Integrasi Kecerdasan Buatan (Artificial Intelligence) dalam Pendidikan Islam: Systematic Literature Review - Yusnita Hasibuan (Jurnal Dirosah Islamiyah, 2026)
The development of artificial intelligence has significantly transformed various sectors, including Islamic education which emphasizes the balance between cognitive, moral, and spiritual aspects, this condition requires adaptation to technological advancements without neglecting Islamic values, this study aims to systematically analyze the development, trends, opportunities, challenges, and pedagogical implications of integrating artificial intelligence into Islamic education, the method used is a Systematic Literature Review with a PRISMA approach involving identification, screening, eligibility, and inclusion of relevant articles from various scientific databases, the results indicate that artificial intelligence enhances learning effectiveness, supports personalized learning, improves educational management efficiency, and promotes creativity and innovation among students, however its implementation still faces challenges such as limited infrastructure, educator readiness, and ethical and theological concerns, the discussion highlights that successful AI integration depends on balancing technological innovation with Islamic values, the conclusion reveals that artificial intelligence has strong potential to sustainably transform Islamic education, but requires a holistic approach to remain aligned with character and spiritual development goals.